Development of Indonesian Language Learning Video Media Based on Multicultural Education for Establish Anti-Ethnic Collection at High School Levels in Singkawang City - Sri Mulyani; Rini Setyowati; Heru Susanto (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
The objectives of this research are (1) Development of video media for multicultural education-based Indonesian learning to build inter-ethnic harmony at the high school level in Singkawang City and (2) the feasibility of video media for Indonesian language learning based on multicultural education to build inter-ethnic harmony at the high school level in the city. Singkawang. This research is a development study using the 4-D model (Four-D developed by Thiagarajan (2011) which includes the stages of defining, designing, developing, and disseminating). This research was carried out in 1 phase with a duration of 1 year The results showed that (1) The stages of development of the development of Multicultural Education-Based Indonesian Language video media for Building Ethnic Harmony at the High School Level in Singkawang City adopted the step or stage of Thiagarajan (2011) which included the defining stage (define) , design, develop, and disseminate (2) The results of the assessment by media experts for all n scores are 4.1 with good category and suitable for use, then based on the assessment of media experts the mean of all aspects is 4.3 with a very good category so that the material is suitable for use.